Artificial Intelligence in Healthcare - Garg, Lalit; Basterrech, Sebastian; Banerjee, Chitresh; Sharma, Tarun K. (Advanced Technologies and Societal Change, 2022)
X, 150 p. 63 illus., 44 illus. in color.